PENGEMBANGAN APLIKASI PEMETAAN ZONASI SEKOLAH DASAR DI KOTA GORONTALO MENGGUNAKAN METODE K-MEANS - Aditya, Farhan; Katili, Muhammad Rifai; Ahaliki, Budiyanto (Gorontalo State University, 2024)
Basic education is a general education that lasts for nine years, consisting of six years in elementary school and three years in junior high school. The aim of basic education is to procide fundamental skills to learners to develop their lives as individuals, community members, citizens, and human beings, and to prepeare them for further education in secondary schools. Every citizens is responsible for ensuring the continuty of educational services. Ironically, in Gorontalo City, the students admission remains the most discussed topic among parents of students every new academic year. This is mainly due to the accessibility of education in certain areas where fraudulent practices in the admission process occur. This situation has left prospective students and parents dissatisfied with the existing system. Therefore, the author considered the need for a method to address this root issue. The method that can be used is the K-means method, which can be applied to the educational system for the students admission. The web-based geoghrapic information feature was developedusing a prototype method. The obtained result include the equal distribution of prospective students in elementary schools based on the zoning mapping of Gorontalo city